ANALISIS PENGARUH SERVICE QUALITY, FOOD QUALITY DAN PERCEIVED VALUE SEBAGAI PREDIKTOR CUSTOMER SATISFACTION PADA RUMAH MAKAN AMPERA BANDUNG - JULIANA .; THEMMY NOVAL; RENO SUSANTO (LP2MTBM MAKARIOZ, 2019)
The purpose of this study are, to explore the predictor of service quality, food quality and perceived value on customer satisfaction. The sample of this research is collected only from a customer who have ever visit and eaten in Ampera restaurant located on Bandung. The hypotheses were tested with primary data (n= 200) collected through structured questionnaire using simple random sampling method. Writer use questionnaire as method of collecting data, The Questionnaire use Likert Scale such as 1 (Strongly Disagree), 2 (Disagree), 3 (Rather Disagree), 4 (Rather Agree), 5 (Agree), 6 (Strongly Agree). The data analysis was conducted using SPSS version 23 and the results are: service quality has a positive and significant predictor of customer satisfaction, food quality has a negative and not significant predictor of customer satisfaction, perceived value has a positive and significant predictor of customer satisfaction